Development of integrated membrane systems for the treatment of olive mill wastewater and valorization of highadded value bioproducts - Bazzarelli, Fabio; Carbone, Vincenzo; Giorno, Lidietta; Piacentini, Emma (My University, 2017)
Nowadays, it is well recognized that advanced clean technologies, able to work in mild conditions and with low energy input are necessary to face challenges in environment protection, ratio nal use of water, production of naturally derived stable bioactive compounds. Membrane technologies fulfill these requirements. Studies are necessary to tune materials and processes for specific applications. The treatment of wastewaters coming from olive oil production is among the critical issues in agro food industry. The present work promoted advances in the development of novel membrane systems for the treatment of olive mill wastewater (OM WW). Th e se waters represent a severe environmental problem due to their high organic load and phytotoxic and antibacterial phenolic compounds, which resist to biological degradation . Additionally, the large volume of OMWW produced in combination with the short discarding time, increases the importance for disposal of this waste. On the other hand, OMWW represents a significant source of polyphenols for health benefits , which can be revalorized and used for medical or agro alimentary purposes. They also represent novel environmentally friendly formulation for chemical m anufacturing. The development of new strategies for the disposal of these by products appears to be extremely useful from an environmental and economic point of view. An advantageous solution is to transform what until now was considered junk to be dispos ed of in resource to be exploited and from which to draw profi t, through the recovery of high added value natural products (bioproducts) and water. In this context, integrated membrane systems can permit the selective recovery of bioactive compounds, such as polyphenols as well as water recovering and purification Moreover, membrane technology is considered a powerful tool for the sustainable industrial development, being able to well respond to the goal of the process intensification strategy” in terms of reduction of the plant size, increase of the plant efficiency, reduction of energy consumption and environmental impact. Nevertheless, one drawback of m embrane filtration of OMWW is the membrane fouling that drastically reduces the process performance. Therefore, OMWW pretreatment upstream of membrane process is necessary to limit fouling phenomena and to increase filtration efficiency. In this thesis, a co mprehensive study from OMWW treatment to biophenols recovery and valorization and water purification by means of integrated membrane process was carried out. Initially, studies focused on the decrease the fouling phenomena. For this purpose, a novel strate gy for a suitable pretreatment of OMWW was identified that permitted to obtain the total removal of suspended solids, through the aggregation and flocculation of particles by maintaining the pH of OMWW at isoelectric point. Secondly, the research focused o n the assessment of the potentiality of OMWW treatment by microfiltration and ultrafiltration process at the laboratory scale. Different organic and inorganic membrane materials were investigated, evaluating the permeation flux and the performance in terms of TOC (Total organic carbon) and polyphenols rejection . Afterwards, processes for OMWW purification aimed at obtaining of biologically active fractions at high concentration as well as their encapsulation were developed. For this purpose pressure-driven membrane processes such as microfiltration (MF) and nanofiltration (NF) and a relatively new membrane operation such as osmotic distillation (OD) were developed on lab scale prototype to obtain and concentrate fractions; membrane emulsification (ME) was st udied for the encapsulation of concentrated fractions. For MF operation, the efficiency of an air back flushing cycle was evaluated to keep constant the permeate flux during the OMWW processing processing. The overall integrated membrane system produced an enriched fraction of polyphenols, as well as a water stream that can be reused for irrigation or membrane cleaning. The highly concentrated polyphenols produced by osmotic distillation, is used as functional ingredients for formulation of water in oil (W/O) emulsions by membrane emulsification. The pulsed back and forward ME has been selected as low shear encapsulation method because it is particularly attractive for the production highly concentrated microemulsions without causing coalescence. The best operative cond itions (transmembrane pressure, wall shear stress) to control particle size and size distribution and obtain high productivity (dispersed phase flux) have been investigated . Water in oil emulsions with a narrow size distribution and high encapsulation effi ciency were obtained. Furthermore, in the present work a n ovel procedure for encapsulation of olive polyphenols with high load into solid lipid particles using traditional method (rotor stator homogenizer) and membrane emulsification was studied. Finally, a productive scale plant of the integrated membrane system was developed and installed at olive mill. The plant included the pre filtration unit, microfiltration, nanofiltration and a further step represented by reverse osmosis. The reverse osmosis has bee n used at large scale instead of membrane distillation due to its higher technology readiness level. Overall, this productive scale plant system proved efficient for fully recovery of biophenols in the retentate stream as well as reclamation of purified wa ter.
Dottorato di Ricerca in Scienze e Tecnologie Fisiche, Chimiche e dei Materiali. Ciclo XXIX
Keywords: Membranes (Technology); Acque reflue